1-Adamantylamine a simple urine marker for screening for third generation adamantyl-type synthetic cannabinoids by ultra-performance liquid chromatography tandem mass spectrometry. (November 2016) - Ford, Loretta T; Berg, Jonathan D
Background: Synthetic cannabinoids (NOIDS) are novel psychotropic drugs (NPS) currently freely sold in the United Kingdom as 'research chemicals'. Detection of NOIDS use is not available in current routine methods. Here we describe a marker which helps determine which patients have used these substances. Methods: In a test case, ultra-performance liquid chromatography mass spectrometry (UPLC-Tof) was used to screen the legal high Herbal Haze II, the contents of hand-rolled cigarettes and five patient samples for NOIDS and their metabolites. Results: Analysis of legal high Herbal Haze II and cigarettes identified the third generation adamantyl-type NOIDS N-(1-adamantyl)-1-pentyl-1H-indazole-3-carboxamide (AKB-48), 5F-AKB-48 and N-adamantyl-1-fluoropentylindole-3-carboxamide (STS-135). Out of 18 potential metabolites, 1-adamantylamine (C10 H17 N) was detected in all five urine samples. This adamantyl-type NOID marker was incorporated into our routine LC-MS/MS urine screen. Out of 14, 436 random urine samples screened over eight months, 296 (2.05%) tested positive for the adamantyl-type NOID marker. Conclusion: We have discovered a urine marker for identifying patients smoking legal high products containing the third generation adamantyl-type NOIDS such as AKB-48 and its fluoropentyl analogue 5F-AKB-48, which are among the most popular NOIDS currently available in legal high products sold in UK. This marker can be incorporated into routine LC-MS/MS drug screening alongside classic drugs of abuse. Positive detection rates for this new legal high marker are greater than for established classic drugs that are routinely screened such as amphetamine. This work highlights the need for a flexible toxicology screening service capable of adapting to changes in drug use such as the growing popularity of legal highs/NPS.